Environmental Education Based on The Potential of Kuala Selangor Nature Park Through Experiential and Joyful Learning-Marine Edutourism - Hayati*, Riza Sativani; Jariah, Ainun; Astutik, Julia (Jurnal IPA & Pembelajaran IPA, 2023)
It is very urgent that environmental education is carried out to increase students' environmental literacy. Effective methods need to be developed to provide environmental experiences while increasing students' contribution to the environment. Malaysia has natural potential as a learning resource for environmental education, one of which is the Kuala Selangor Nature Park. This research aims to 1) conduct a study of the potential of the Kuala Selangor National Park mangrove ecosystem for the development of environmental education learning tools and 2) implement the experiential and joyfull learning-marine edutourism (EJoy-ME) learning model based on the potential of Kuala Selangor National Park to increase students' environmental literacy. The method used was observation of the natural resource potential of Kuala Selangor Nature Park and quasi-experimentation of the EJoy-ME learning model. The results of the study show that Kuala Selangor Nature Park has the potential to be developed as a learning resource for environmental education through EJoy-ME. The implementation of EJoy-ME has been proven to be able to increase students' environmental literacy. The EJoy-ME learning model also received positive responses from students, namely providing satisfaction with environmental materials, satisfaction with the learning process, and providing a pleasant learning experience